ISSUES OF THE INTRODUCTION OF MODERN INNOVATIVE TECHNOLOGIES AND THE DEVELOPMENT OF STATE PROGRAMS IN THE FIELD OF LAW - Nasiba Niyazova (Scholar Express Journals, 2024)
This article examines the issues of the introduction of modern innovative technologies in the field of law, which help automate work in the field of jurisprudence. The author highlights Government programs in the field of jurisprudence in Uzbekistan such as "Electronic government", e-imzo, Eadvokat, "my government" (my gov), "my.sud.uz ", "Electronic Notary", which were created in order to simplify the access of individuals and legal entities
Keywords: Digitalization; government program; automation; modern technologies